How Leadership Commitment Shapes the Impact of Scope Management Programs on Team Accountability - Ikhsan Nendi; Amelia Amelia (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Organizations worldwide continue to experience scope-related project failures despite substantial investment in formal governance programs, indicating that structural mechanisms alone are insufficient to guarantee accountability outcomes. Objective: This study investigates the moderating role of leadership commitment in the relationship between scope management programs and team accountability within corporate settings. Drawing on agency theory, stakeholder theory, and the resource-based view, the research examines how executives' visible endorsement, resource allocation, and behavioral modeling amplify or attenuate the effectiveness of formal scope management initiatives. Methods: Using a quantitative survey design, data were collected from 320 project managers and team leaders across manufacturing, financial services, and technology sectors in Indonesia. Structural equation modeling (SEM) with SmartPLS 4.0 was employed to test the hypothesized relationships. Results: Findings reveal that leadership commitment significantly moderates the scope management–team accountability relationship (β = 0.412, p < 0.001), with high leadership commitment more than doubling the positive effect of scope management programs. The model explains 56.1% of the variance in team accountability (R² = 0.561). Conclusions: The study contributes to project management theory by integrating leadership as a boundary condition and offers practical guidance for organizations seeking to enhance accountability through governance reforms. Practically, the findings guide executives to pair scope-governance investments with structured leadership-development initiatives that strengthen accountability outcomes.